Assessment of Dry Eye in Post-Menopausal Women - Riaz, Irum; Awan, Muhammad Anwar; Munir, Zohra; Khan, Zaryab; Sabir Khan, Muhammad Aleem; Mehronisa (Medical Journal of South Punjab, 2024)
Objective: To find out the prevalence and severity of dry eye in Post-Menopausal Women. Methodology: This cross-sectional study included 59 participants who had been diagnosed with menopause based on their medical history. After acquiring signed consent, Patients were inquired about any ocular complaints of dry eye, and a Schirmer test was done using an anesthetic agent after they were comfortable. The ethics committee had already given their approval. Result: The current study included 59 post-menopausal women. The overall incidence of dry eye disease in postmenopausal women was found to be 43 (72.9%), which was statistically significant (p<0.05). The majority of postmenopausal women with dry eyes were between the ages of 60–64 years old (83.3%). Among 43 (72.9%) postmenopausal women, 23.6% had mild dry eye, 51.16% had moderate dry eye, and 25.58% had a severe dry eye. DED becomes more severe as the patient becomes older and the menopause lasts longer. Hormonal changes, dietary deficiencies, environmental variables, underdiagnoses of illness, and poor compliance were the most common causes of postmenopausal women’s dry eyes. Conclusion: Our study was compared to previous dry eye investigations, and the results were determined to be comparable. Hence, dry eye should be tested and treated periodically. Early diagnosis of dry eye can reduce the risk of visual impairment and can improve the general performance of postmenopausal women.